Estimated effect of secondary screening for hip dislocation. Issue 12 (3rd July 2020) - Wenger, Daniel; Tiderius, Carl Johan; Düppe, Henrik
Abstract : Objectives: To quantify the effect of secondary screening for hip dislocations. Design: Retrospective analysis of hospital files from participants in a prospectively collected nationwide registry. Setting: Child healthcare centres and orthopaedic departments in Sweden. Participants: Of 126 children with hip dislocation diagnosed later than 14 days age in the 2000–2009 birth cohort, 101 had complete data and were included in the study. Interventions: The entire birth cohort was subject to clinical screening for hip instability at 6–8 weeks, 6 months and 10–12 months age. Children diagnosed through this screening were compared with children presenting due to symptoms, which was used as a surrogate variable representing a situation without secondary screening. Main outcome measures: Age at diagnosis and disease severity of late presenting hip dislocations. Results: Children diagnosed through secondary screening were 11 months younger (median: 47 weeks) compared with those presenting with symptoms (p<0.001). Children diagnosed through secondary screening had 11% risk of having a high (severe) dislocation, compared with 38% for those diagnosed due to symptoms; absolute risk reduction 27% (95% CI: 9.7% to 45%), relative risk 0.28 (95% CI: 0.11 to 0.70). Children presenting due to symptoms had OR 5.1 (95% CI: 1.7 to 15) of having a high dislocation, and OR 11 (95% CI: 4.1 to 31) of presenting at age 1 year or older, compared with the secondary screening group. The secondary screening was able to identify half of the children (55%, 95% CI: 45% to 66%) not diagnosed through primary screening. Conclusions: Secondary screening at child healthcare centres may have substantially lowered the age at diagnosis in half of all children with late presenting hip dislocation not diagnosed through primary screening, with the risk of having a high dislocation decreased almost to one-quarter in such cases.